PENERAPAN NILAI-NILAI TOTAL QUALITY MANAGEMENT (TQM) DALAM PENGELOLAAN SUMBER DAYA MANUSIA DI MADRASAH - Sri Haryati (Cendekia: Kependidikan dan Kemasyarakatan, 2013)
Generally Madrasah has weak competitiveness in many sectors. One of them is the availability and management of human resources that is less optimal. This has led to the low professionalism of human resources who manage education institutions of Madrasah in Indonesia. As a result, the quality of Madrasah is still left behind by other public educational institutions. Some efforts to achieve a qualified Madrasah especially in terms of availability of professional human resources have been experiencing significant constraints, so that the level of public and government appreciation is relatively less. To improve the performance of Madrasah which is currently underestimated compared to the public schools, it is suggested to implement Total Quality Management (TQM) simultaneously. The application of TQM in Madrasah as Islamic education institution is obviously important to improve and maintain the quality of Madrasah. The implementation of human resource management at Madrasah is very effective in managing the teachers and education staffs in establishing and maintaining the quality of institutions. This is due to the fact that human factor (teacher and education staff) is the most strategic element in the management of Madrasah as Islamic educational institutions. روح المنافسة  في المدارس الدينية عامة ضعيفة. والسبب في ذلك ضعف وجود الموارد البشرية غير الفعّالة. هذا أدي إلى أن مهنية الموارد البشرية المنظم للمدارس الدينية في إندونيسيا – أغلبها – ضعيفة. لذا فإن نوعية وجودة المنظمين للمدارس الدينية متأخرة إذا قورنت بالمنظمين للمدارس العامة. والمحاولة لإيجاد المدارس الدينية الجيدة لا تزال فيها عوائق كثيرة، خاصة فيما يتعلق بتوفر الموارد البشرية المهنية حتى يكون اهتمام وقبول المجتمع والحكومة  بها ناقص. ولترقية انجازات المدارس الدينية يحسن تطبيق TQM متواصلا. وهذا التطبيق – في المدارس الدينية – مهمّ جدا، لأنه به يمكن أن تدارالمدارس الدينية مهنيا لترقية جودتها والمحافظة على هذه الجودة. وتطبيق إدارة الموارد البشرية في المدارس الدينية فعال في تنظيم المدرسين والقائمين بالتربية في تكوين جودة المدارس الدينية والمحافظة عليها، لأن العنصر الإنساني هو عنصر هام في تنظيم وإدارة المؤسسة التربوية الإسلامية (المدارس الدينية) .